First-line checkpoint inhibitor therapy in metastatic acral lentiginous melanoma compared to other types of cutaneous melanoma: a multicenter study from the prospective skin cancer registry ADOREG - Reinhard, Sören; Utikal, Jochen; Zaremba, Anne; Lodde, Georg; von Wasielewski, Imke; Klespe, Kai Christian; Meier, Friedegund; Haferkamp, Sebastian; Kähler, Katharina C.; Herbst, Rudolf; Gebhardt, Christoffer; Sindrilaru, Anca; et al. (European journal of cancer, 2025)
Background - Melanoma is the main cause of skin cancer-related death. Treatment with immune checkpoint inhibitors (CPI) has improved the prognosis in recent years. However, subtypes of melanoma differ in their response. Acral lentiginous melanoma (ALM) has a worse prognosis compared to cutaneous melanoma other than ALM (CM) and is therefore of particular relevance. - Aims - To evaluate the efficacy of CPI in first-line treatment of patients with advanced ALM compared CM. - Methods - Retrospective analysis of patients with metastatic ALM (n=45) or CM (n=328) who received first-line CPI therapy from the multicenter prospective skin cancer registry ADOREG. Study endpoints were best overall response (BOR), progression-free survival (PFS) and overall survival (OS). - Results - ALM patients had significantly higher rates of ulcerated tumors, loco regional metastases and fewer BRAF-mutated tumors compared to CM patients. Combined CPI was administered in 48.9% ALM patients and 39.3% of CM patients, while the remaining patients received PD-1 monotherapy. OS trended to be shorter in patients with ALM (18.1 vs. 43.8 months, p=0.10) with no significant differences in PFS (7.0 vs. 11.5 months, p=0.21). In patients with CM, median OS with combined CPI was not reached, whereas the median OS after PD-1 monotherapy was 37.8 months (p=0.22). Conversely, in patients with ALM, OS with combined CPI was 17.8 months, compared to 26 months with PD-1 monotherapy (p=0.15). There were no significant differences in BOR between patients with ALM or CM. - Conclusion - Analysis of this real-world cohort of patients with metastatic melanoma showed a trend towards poorer survival outcomes upon first-line treatment with CPI in ALM compared to cutaneous melanoma of other subtypes.
Online veröffentlicht: 15. März 2025, Artikelversion: 22. März 2025
Gesehen am 28.05.2025